ДОКТРИНАЛЬНІ ПРОБЛЕМИ ІНСТИТУТУ НЕГЛАСНИХ СЛІДЧИХ (РОЗШУКОВИХ) ДІЙ - Корнієнко, Михайло Васильович, Тертишник Володимир Митрофанович (SUPREMANCE OF LAW, 2016)
In the article reveals the problems of legal certainty procedural undercover investigation form (investigative) action in criminal procedure of Ukraine, the law of evidence and the optimization of the Institute investigative actions through the prism of harmonizing public and private interests are conceptual models of legal form separate undercover investigations.
Keywords: investigations; evidentiary; procedural right form; legal certainty